Obtaining bioelectricity using a plantmicrobial fuel cell - Besarab, Y.V. (Problems of Environmental Biotechnology, 2023)
Demand for energy around the world is growing rapidly due to the development of technology. The emergence of new sources of renewable energy that would be safe for the environment and available for use becomes necessary. One of the ways to produce bioelectricity is to use microbial fuel cells (MFC). MFC technology uses an approach where electrochemically active microorganisms are used to generate electricity by oxidizing the organic components of environmental waste and renewable biomass. But one of its disadvantages is the complete use of the substrate by bacteria, which can lead to a stoppage of electricity production for a certain time. The concept of including plants in the anode area as a source of substrate for bacteria helps to solve this problem.